MORPHOLOGY AND MORPHOMETRY OF INTERNAL GENITALIC ORGANS OF TWO SPECIES OF GENUS AGYLLA WALKER (LITHOSIINAE : ARCTIIDAE) - KIRTI, JAGBIR SINGH; SODHI, JAGPREET SINGH (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2005)
Internal genitalic organs of two species i.e. antica Walker and devisa Walker of genus Agylla Walker have been studied and illustrated for the first time. Morphological and morphometrical measurements of these organs have also been discussed in this manuscript.